Back Cover Image. Issue 3 (8th April 2019) - Adams, Shaun; Grün, Rainer; McGahan, David; Zhao, Jian‐Xin; Feng, Yuexing; Nguyen, Ai; Willmes, Malte; Quaresimin, Michael; Lobsey, Brett; Collard, Mark; Westaway, Michael C.
Abstract : Back Cover Legend : The cover image is based on the Research Article A strontium isoscape of north‐east Australia for human provenance and repatriation by Shaun Adams et al., https://doi.org/10.1002/gea.21728 . Cover image © Shaun Adams.